Control of phospholipid peroxidation and enzyme activity losses in mitochondria by antioxidants (Revista Española de Fisiología, 1974)
Control of Phospholipid Peroxidation and Enzyme Activity Losses in Mitochondria by Antioxidants. Rev. esp. Fisiol., 30, 127-132. 1974.The antioxidant efficiency of BHT (2,6-tert-butyl-4-methylphenol) and of thyroxine in preventing phospholipid peroxidation, membrane disaggregation and losses of enzyme activity has been studied in suspensions of inner mitochondrial membranes from rat liver incubated in the presence of 1 mM ascorbate or 0.8 mM cysteine. The addition of BHT, at zero-time and at a concentration of 5 X 10-s M in the case of ascorbate, or of 5 X 10_0 M in the case of cysteine, completely inhibited lipid peroxidation and related processes. If BHT was added at a later time during the incubation, different degrees of inhibition were obtained. Similar effects were observed with 10~s M thyroxine. These results suggest the possibility of using a simple method in the study of associations between phospholipids and membrane-bound enzymes.